The association of 25(OH)D, interleukin-4, interleukin-5, and interleukin-13 levels with the burden of soil-transmitted helminth infection in stunted children aged 24–59 months - Riyadi Adrizain; Monika Verena Nagari; Djatnika Setiabudi; Afiat Berbudi; Budi Setiabudiawan (Autoimmunity, 2024)
Soil-transmitted helminth (STH) among children aged 24–59 months is one cause of chronic infection that could lead to stunting. The association of 25(OH)D and immune responses during chronic infection in stunted populations has not yet been well established. An association study of case–control data was conducted in Bandung district from October 2019 to January 2023. Sociodemographic factors, stool samples, and serum levels of 25(OH)D, interleukin-4 (IL-4), interleukin-5 (IL-5), and interleukin-13 (IL-13) were assessed. Statistical analysis was performed to evaluate the prevalence and association of 25(OH)D, IL-4, IL-5, and IL-13 with the burden of STH infection in stunted children. In total, 401 stunted children were recruited. A higher burden of STH infection was found for lower levels of IL-5 (r = −0.477; p = 0.004) and IL-13 (r = −0.433; p = 0.028). Thus, 25(OH)D, IL-4, IL-5, and IL-13 play a role in the burden of STH infection.